The exploration of the potential mechanism of oxymatrine-mediated antipruritic effect based on network pharmacology and weighted gene co-expression network analysis - Luo, Zhenhui; Zhao, Tingting; Yi, Mengqin; Wang, Tingting; Zhang, Zhenglang; Li, Wenbin; Lin, Na; Liang, Shangdong; Verkhratsky, Alexei; Nie, Hong (Frontiers in Pharmacology, 2022)
Objective: To investigate oxymatrine (OMT)'s possible targets and processes in the treatment of pruritus. Methods: Matrine component target genes were obtained from the PharmMapper database; itching and inflammation-related gene targets were obtained from Gene Cards and OMIM. The OMT, pruritus, and inflammatory disease targets were added to the String database, and a drug-disease target PPI network was built and assessed. A drug-target-pathway network is eventually established using core target gene screening and functional enrichment. At the same time, the GEO database was utilized to extract RNA-seq high-throughput sequencing data from atopic dermatitis patients and perform weighted gene co-expression network analysis (WGCNA). With 125 direct targets, the whole network of drug medicine-component-direct target-indirect target-pathway was established. The MAPK signaling pathway, the PI3K-AKT signaling pathway, the metabolism-related liver disease pathway, and other associated pathways were shown to be involved in the mechanism of OMT controlling inflammation and anti-pruritus. Using a combination of WGCNA and network pharmacology analysis, three genes were identified: LCK, AMD1, and MAPKAPK2. These three genes may have a role in pruritus onset and progression. OMT was shown to be linked to the signal location of MAPKAPK2 in the upstream MAPK signaling pathway. Further research revealed that OMT may control LPS-induced macrophage inflammation via the MAPK signaling pathway. Conclusion: By modulating the MAPK signaling pathway and altering biological processes such as inflammation, OMT supplied the potential therapeutic targets for the treatment of pruritus.